Quasi-static/dynamic energy absorption characteristics and micromechanical behavior of Al/Ep cast metal braided tubular structures - Enling Tang; Chaohua Yue; Ruizhi Wang; Yafei Han; Chuang Chen; Mengzhou Chang; Kai Guo; Liping He (Journal of Materials Research and Technology)
As a low-density, high-strength material with high energy release potential, Al/Ep cast metal braided tubes have a wide range of application prospects in the combatant shell, which is one of the most important means to realize the integrated destructive effect of kill and blast. In this paper, Al/Ep composites with mass ratios of 3:7, 4:6 and 5:5 were prepared, and the intrinsic model of Al/Ep was established by studying its quasi-static and dynamic mechanical properties. The Al/Ep cast three-dimensional braided metal skeletons were used to obtain the required cast braided tubes with different mass ratios, and the destruction behaviors of the tubes under axial and radial compressive loads were analyzed by a combination of experimental and numerical simulations. The results show that the addition of Al particles can significantly improve the elastic-plastic properties of Al/Ep composites, and the energy storage and absorption capacities are positively correlated with the ratio of the relative contents of Al powder. When the mass ratio of Al powder to epoxy resin is 5:5, the energy absorption of Al/Ep composites is 23.16 MJ/m3, which is optimal among similar specimens and much higher than that of pure epoxy resin materials (the energy absorption of epoxy resin is 9.63 MJ/m3). The strength of binary resin matrix composites is improved, and the intrinsic models of three kinds of different mass ratios of Al/Ep composites are obtained. The intrinsic models of various Al/Ep cast braided tubes with crushing force efficiency CFE, energy absorption capacity, and specific energy absorption SEA decreased with the ratio of mass occupied by the braided filaments.